Surakarta Gastronomy in Student Presentations to Increase Self-Confidence and Reduce Speaking Anxiety - Ika Martanti Mulyawati (UIN Raden Mas Said Surakarta, Indonesia, 2025)
This study aims to analyze how Surakarta gastronomy can be utilized as a cultural context to reduce students' speaking anxiety and increase their confidence in academic presentations. The phenomenon of speaking anxiety remains a dominant issue for Indonesian Language Education students, especially when they have to demonstrate their oral skills in front of the class. This anxiety generally arises from performative pressure, fear of making mistakes, and a lack of relevant and meaningful speaking experiences. Given the importance of context in language learning, the Project-Based Learning (PjBL) approach is considered an effective strategy because it emphasizes authentic experiences, collaboration, and the production of concrete artifacts. This qualitative study used presentation observation, in-depth interviews, visual documentation, and performance assessment to collect data. Data analysis was conducted using the Miles and Huberman model through the stages of reduction, presentation, and conclusion drawing. The results showed that using Surakarta gastronomy as a project context was able to reduce students' speaking anxiety by providing a topic that was familiar, emotionally close, and rich in cultural values. Through involvement in the culinary project, students appeared more confident, more expressive, and better able to convey ideas coherently. Learning also became more collaborative and dialogic, thus providing a safe space for students to experiment with language. These findings confirm that gastronomy-based PjBL is an innovative and relevant pedagogical alternative for teaching speaking skills in higher education. Penelitian ini bertujuan untuk menganalisis bagaimana gastronomi Surakarta dapat dimanfaatkan sebagai konteks budaya untuk mengurangi kecemasan berbicara mahasiswa dan meningkatkan kepercayaan diri mereka dalam kegiatan presentasi akademik. Fenomena kecemasan berbicara masih menjadi persoalan dominan bagi mahasiswa Tadris Bahasa Indonesia, terutama ketika harus menampilkan kemampuan lisan di depan kelas. Kecemasan ini umumnya muncul akibat tekanan performatif, ketakutan melakukan kesalahan, serta minimnya pengalaman berbicara yang relevan dan bermakna. Mengingat pentingnya konteks dalam pembelajaran bahasa, pendekatan Project-Based Learning (PjBL) dipandang sebagai strategi efektif karena menekankan pengalaman autentik, kolaborasi, dan produksi artefak konkret. Penelitian kualitatif ini menggunakan observasi kegiatan presentasi, wawancara mendalam, dokumentasi visual, serta penilaian performansi untuk mengumpulkan data. Analisis data dilakukan menggunakan model Miles dan Huberman melalui tahap reduksi, penyajian, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa penggunaan gastronomi Surakarta sebagai konteks proyek mampu menurunkan kecemasan berbicara mahasiswa dengan menyediakan topik yang familiar, dekat secara emosional, dan kaya nilai budaya. Melalui keterlibatan dalam proyek kuliner, mahasiswa tampak lebih percaya diri, lebih ekspresif, dan lebih mampu menyampaikan gagasan secara runtut. Pembelajaran juga menjadi lebih kolaboratif dan dialogis, sehingga memberikan ruang aman bagi mahasiswa untuk bereksperimen dengan bahasa. Temuan ini menegaskan bahwa PjBL berbasis gastronomi merupakan alternatif pedagogis yang inovatif dan relevan untuk pembelajaran keterampilan berbicara di perguruan tinggi.